ASPEK YURIDIS PENDAFTARAN PERALIHAN HAK ATAS TANAH KARENA PEWARISAN - Rofiqah Rahmi; Sudjito Sudjito (Jurnal Ilmu Hukum, 2020)
This research is intended to find out in-depth the juridical aspects of land registration due to inheritance. Two issues were examined, namely: (1) Why were the requirements for the Deed of Sharing Common Rights mandatory and the Deed of inheritance rejected when registration of the transfer of title to the land due to inheritance? (2) What are the legal consequences of the Deed of Sharing of Joint Rights in the registration of the transfer of title to the certified land due to inheritance? The study was conducted by a combination of literature research and field research. Data were analyzed qualitatively. The results showed: (1) the Magelang Land Office requires that all inheritance of land rights be processed first through inheritance, followed by the making of the Deed of Sharing Common Rights, and then registered, on the grounds that the computerized system is not yet perfect. So it's not a legal problem. (2) The legal consequences are that the heirs are forced to pay tax 2 (two) times. This matter is burdensome to the heirs.